Helium isotope, C/3He, and Ba‐Nb‐Ti signatures in the northern Lau Basin: Distinguishing arc, back‐arc, and hotspot affinities. (28th April 2015) - Lupton, John; Rubin, Ken H.; Arculus, Richard; Lilley, Marvin; Butterfield, David; Resing, Joseph; Baker, Edward; Embley, Robert
Abstract The northern Lau Basin hosts a complicated pattern of volcanism, including Tofua Arc volcanoes, several back‐arc spreading centers, and individual "rear‐arc" volcanoes not associated with these structures. Elevated 3He/4He ratios in lavas of the NW Lau Spreading Center suggest the influence of a mantle plume, possibly from Samoa. We show that lavas from mid‐ocean ridges, volcanic arcs, and hotspots occupy distinct, nonoverlapping fields in a 3He/4He versus C/3He plot. Applied to the northern Lau Basin, this approach shows that most of Lau back‐arc spreading systems have mid‐ocean ridge 3He/4He‐C/3He characteristics, except the NW Lau spreading center, which has 3He/4He‐C/3He similar to "high 3He" hotspots such as Loihi, Kilauea, and Yellowstone, but with slightly lower C/3He. Niua seamount, on the northern extension of the Tofua Arc, falls squarely in the arc field. All the NE Lau rear‐arc volcanoes, including the recently erupting West Mata, also have arc‐like 3He/4He‐C/3He characteristics. Ba‐Nb‐Ti contents of the lavas, which are more traditional trace element indicators of mantle source enrichment, depletion, and subduction input, likewise indicate arc and hot spot influences in the lavas of the northern Lau Basin, but in a more ambiguous fashion because of a complex prior history. This verifies that 3He/4He‐C/3He systematics are useful for differentiating between mid‐ocean ridge, arc, and hotspot affinities in submarine volcanic systems, that all three of these affinities are expressed in the northern Lau Basin, and provides additional support for the Samoan plume influence in the region.